The 3rd International conference on humanities (PAPK2025) - Saidatul Nornis Hj. Mahali; Shaffarullah Abdul Rahman; Aishah Tamby Omar; Muhammad Azwan Kamaruddin; Herbert Buhod Stephen Naidi (Penerbit Universiti Malaysia Sabah, 2025)
The editorial committee of PAPK2025 are glad to present this volume of research proceedings with the title of Empowerment of Human Values: Proceedings of the 3rd International Conference on Humanities (PAPK2025). This is the third conference after the previous ones that have been held on 2017 and 2019. On behalf of PAPK2025, we would like to express our sincere appreciation to all the authors for their contribution to this book of proceedings. These contributions reflect the various topics of research from the fields of language studies, linguistics and professional societies that were presented during the conference held on the 1st of July 2025. There are 64 articles, 46 Malay articles and 18 English. These articles cover different sub-themes of the conference, such as i) Language, Linguistics and Communication; ii) Education and Learning; iii) Education and Digital Innovation; iv) Arts, Culture and Heritage; v) Social, Community and Gender; vi) Religion, Dakwah & Fiqh; vii) Politics and Governance; viii) Environment and Ecosystem; and ix) Technology and Digitalisation.